(untitled) (The Review of Diabetic Studies, 2024)
The integration of laboratory, nursing, and social services data within Electronic Health Records (EHRs) has become a defining element of healthcare digital transformation. This integrative review synthesizes studies published between 2020 and 2024 to identify best practices that enhance data accuracy, interoperability, and multidisciplinary collaboration across healthcare settings. A systematic search of PubMed, Scopus, CINAHL, Web of Science, and Google Scholar yielded 38 eligible studies addressing laboratory data management, nursing documentation, and social services data integration. Findings reveal that implementing standardized frameworks such as HL7-FHIR, LOINC, and ISO 15189 significantly improves laboratory interoperability and reporting accuracy. In nursing, structured documentation using NANDA-I, NIC, and NOC taxonomies enhances communication, decision support, and compliance with quality standards. The inclusion of social determinants of health (SDOH) within EHRs fosters holistic care planning and strengthens community-based interventions. Cross-domain themes emphasize the importance of governance, workforce training, and national policy alignment. Collectively, these findings demonstrate that EHRs achieve their full potential when supported by strong governance, interoperability standards, and informed clinical participation. Aligning these practices with Saudi Arabia’s Vision 2030 digital-health strategy can accelerate the development of a unified, patient-centered health information ecosystem.